A history of Adivasi women in post-independence Eastern India : the margins of the marginals - De, Debasree (SAGE Publications, 2018)
Introduction -- Demystifying Adivasi women: some epistemological issues -- Changing livelihood pattern of Adivasi women in West Bengal -- Adivasi Rejas in Bihar -- Adivasi women and land rights in Jharkhand -- Adivasi women and destructive development in Odisha -- Marginalizing Adivasi women: the process of cultural silencing -- Epilogue.